COLLABORATION-BASED SUPPORT PROVISION MODELS FOR CHILDREN WITH SPECIAL EDUCATIONAL NEEDS - Kantanavičiūtė, Rita; Tomėnienė, Laima (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article aims to reveal collaboration-based support provision models for a child with special educational needs and his/her family in Lithuania. The qualitative research method used was a semi-structured interview. The participants of the research were special educators and speech therapists providing support to school-age children with special educational needs. The obtained results of the research helped to reveal children support specialists’ attitude towards collaboration-based support provision to a child with special educational needs and his/her family in Lithuania. The research revealed the importance and opportunities of the implementation of interprofessional coordinated support based on interprofessional collaboration, referring to the experience of speech therapists and special educators providing support to a school-age child with special educational needs and his/her family.